Treatment of Neuropathic Pain with 5% Lidocaine-Medicated Plaster: Five Years of Clinical Experience - Claire Delorme; Marie L Navez; Valérie Legout; Rodrigue Deleens; Dominique Moyse (Pain Research and Management)
BACKGROUND: Neuropathic pain is often severe and adversely affects patients’ quality of life.